ANALISIS KEBUTUHAN AWAL PENGEMBANGAN MEDIA POP UP BOOK BERBASIS BUDAYA LOKAL TERHADAP LITERASI SAINS DI SEKOLAH DASAR - Silvi, Risna; Suryanti; Suprapto, Nadi; Hendratno; Istiq’faroh, Nurul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Scientific literacy is essential to face the challenges of the 21st century. It must be taught to train students in thinking, analyzing, and collaborating to solve problems. However, according to PISA, the scientific literacy of Indonesian students is categorized as low. This is primarily due to unengaging learning processes. Students need interesting learning media to improve their scientific literacy. One potential medium is a pop-up book based on local culture. This study aims to identify the necessary requirements for developing a pop-up book based on local culture to enhance scientific literacy in elementary schools. The research employs a qualitative method with a descriptive approach, using observation and interview instruments conducted in Grade V at UPT SDN 207 Gresik. The findings indicate that teachers have not yet used engaging media for ecosystem topics, nor have they incorporated Gresik's local culture into the learning process. Effective learning media should be able to attract students' interest, connect with local culture, promote critical thinking skills, and improve scientific literacy. Based on the analysis, it is concluded that there is a need for learning media that aligns with students' developmental stages. A pop-up book based on local culture can enhance students' interest in learning ecosystems while fostering their understanding of local culture. The development of such a medium is crucial to meet the learning needs of students.